Proteomics Analysis of Aqueous Humor and Rejected Graft in Pig-to-Non-Human Primate Corneal Xenotransplantation - Oh, Jae Won; Yoon, Chang Ho; Ryu, Jin Suk; Kim, Kwang Pyo; Kim, Mee Kum (Frontiers in Immunology, 2022)
Although pig-to-nonhuman primate (NHP) corneal xenotransplantation has shown long-term graft survival, xenogeneic antigen-related immune responses are still stronger than allogenic antigen-associated responses. Therefore, there is an unmet need to investigate major rejection pathways in corneal xenotransplantation, even with immunosuppression. This study aimed to identify biomarkers in aqueous humor for predicting rejection and to investigate rejection-related pathways in grafts from NHPs transplanted with porcine corneas following administration of steroids combined with tacrolimus/rituximab. NHPs who had received corneas from wild-type (WT) or α-1,3-galactosyltransferase gene-knockout (GTKO) pigs were divided into groups with or without rejection according to clinical examinations. Liquid chromatography-mass spectrometry (LC-MS) was used to analyze the proteomes of corneal tissues or aqueous humor. The biological functions of differentially expressed proteins (DEPs) were assessed using Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) for pathways and protein–protein interaction network analysis. Among the 66 DEPs in aqueous humor, complement proteins (C3, C5, and C9) and cholesterol metabolic proteins (APOA1 and APOA2) were related to xenogeneic rejection as biomarkers, and alternative pathways of the complement system seemed to be important in xenogeneic graft rejection. Among 416 DEPs of the cornea, NF-κB1 and proteosomes (PSMD7, PSMA5, and PSMD3) seemed to be related with xenogeneic graft rejection. Additionally, oxidative phosphorylation and leukocyte activation-related pathways are involved in rejection. Overall, our proteomic approach highlights the important role of NF-κB1, proteosomes, oxidative phosphorylation, and leukocyte activation-related inflammation in the cornea, and the relevance of complement pathways of the aqueous humor as a predictive biomarker of xenogeneic rejection.